Effectiveness of Sprayed Bioactive Fruit Extracts in Counteracting Protein Oxidation in Lamb Cutlets Subjected to a High-Oxygen MAP - Morcuende, David; Vallejo Torres, Christian; Ventanas, Sonia; Martínez, Sandra Luz; Ruiz, Silvana Cecilia; Estévez, Mario (MDPI, 2023)
High-oxygen packaging atmosphere (High-Ox-MAP) promotes meat protein oxidation and leads to texture deterioration. This study was conceived to assess the extent to which sprayed fruit extracts could inhibit the oxidative damage to proteins in lamb cutlets subjected to High-Ox-MAP (10 days/4 °C) and subsequent roasting (10 min/180 °C). Extracts from oaknut (Quercus ilex subsp. ballota; QI), rose hips (Rosa canina L.; RC), common hawthorn (Crataegus monogyna Jacq.; CM) and strawberry tree (Arbutus unedo L.; AU) were characterized for bioactive compounds (phenolic subclasses, tocopherols and ascorbic acid) and in vitro bioactivities. While the four fruits showed relevant antioxidant potential, CM had the highest phenolics and tocopherol content and that was reflected in efficient antiradical activity. The in vitro activity of this fruit to inhibit meat protein oxidation was, however, lower than that displayed by the other fruits. Taking the results altogether, CM was also found to be most efficient in protecting lamb cutlets from lipid oxidation. All fruits were able to inhibit thiols oxidation except RC, which seemed to reduce protein thiols. Among fruits, QI was the most efficient in protecting lamb cutlets against protein carbonylation as a plausible involvement of ellagitannins. The inhibition of protein oxidation by QI was reflected in significantly lower instrumental hardness in cooked lamb cutlets. Spraying lamb cutlets with extracts from QI, RC and CM improved consumers’ purchase intention after chilled storage. This antioxidant strategy seems to be a feasible and efficient solution to the pro-oxidative effects caused by High-Ox-MAP in red meat.